KINERJA KOMODITAS ELEKTRONIKA INDONESIA 1981-1995: PENDEKATAN KEUNGGULAN KOMPARATIF - Ahmad Jamli; Ryan Rizaldy (Journal of Indonesian Economy and Business (JIEB), 1998)
Electronic industry has become one of the alternatives of the high value added industrial development scheme. This paper examines the comparative advantage ofIndonesian electronic commodities, utilizing of three indices of RCA (Revealed Comparative Advantage): the net export to total trade ratio, the world export share(WESij), and the export import ratio (EIR ij). In order to assess changes in comparative advantage in relation to growth of world imports, the changes of WESij vector over the period studied is correlated with the world demand growth; and, to determine whether net protection has increased or not, the WESij vector is correlated with EIRij vector.The result shows that from the period of 1981-1995, there are only two commodities which show good performance. In general we can conclude that, the commodities haven't shown any good competitive performance yet. The weakness as on the industrial development scheme and policy making for the development of Indonesian electronic Industry in the future are discussed.